On the logic of values - Dries, M (Penn State University Press, 2010)
This article argues that Nietzsche's transvaluation project refers not to a mere inversion or negation of a set of values but, instead, to a different conception of what a value is and how it functions. Traditional values function within a standard logical framework and claim legitimacy and "bindingness" based on exogenous authority with absolute extension. Nietzsche regards this framework as unnecessarily reductive in its attempted exclusion of contradiction and real opposition among competing values. I propose a nonstandard, dialetheic model of valuation that requires a value to be both true and false as well as neither true nor false.